Filsafat Pendidikan dalam Mengembangkan Karakter Siswa Kelas 5 SDN Walikukun: Landasan Nilai dan Implementasinya di Era Digital - Khairun Nisa; Desty Endrawati Subroto; Dwi Nutfiah Damayanti; Eva Saifatul Munawaroh; Tya Adelia (Lembaga Pengembangan Kinerja Dosen, 2025)
The objective of this study is to design an appropriate strategy in instilling character values ​​in grade 5 students of SDN Walikukun, with an emphasis on strengthening the values ​​of responsibility, discipline, honesty, and cooperation. The study employed literature studies and qualitative data analysis, which resulted in the conclusion that it is very important for character building in elementary schools to be implemented systematically and sustainably. These efforts need to involve the active role of various parties, such as teachers, parents, schools, and the surrounding environment. The implementation strategy includes integrating character values ​​in the teaching and learning process, habituating positive daily actions, role models from teachers, and monitoring student development through behavioral documentation. In addition, democratic and communicative parenting patterns greatly influence children's character formation, especially if adjusted to the child's innate personality type which can be recognized through approaches such as genetic personality. Simple digital technology can also be used as a supporting medium for character education, although there are still obstacles in the form of limited facilities and infrastructure. The results obtained from this study are hoped to be used as a reference in the implementation of relevant and effective character education at SDN Walikukun.